Gene expression profiling of humans under exertional heat stress: Comparisons between persons with and without exertional heat stroke. (October 2019) - Ren, Ming Qiang; Kazman, Josh B.; Abraham, Preetha A.; Atias-Varon, Danit; Heled, Yuval; Deuster, Patricia A.
Abstract: Exertional heat stroke (EHS) is a leading cause of preventable morbidity and mortality among both athletes and warfighters. Therefore, it is important to find blood biomarkers to predict susceptibility to EHS. We compared gene expression profiling from blood cells between two groups of participants – those with and those without a history EHS – by using genome-wide microarray analysis. Subjects with a history of EHS (n = 6) and non-EHS controls without a history of EHS (n = 18) underwent a heat tolerance test and a thermoneutral exercise challenge on separate days. The heat tolerance test comprised of 2-h of walking, at 5 km/h and 2% incline, with ambient conditions set at 40 °C, 40% relative humidity; the thermoneutral test was similar, but had ambient conditions set at 22 °C. Next, we examined gene expression profiles, quantified based on arithmetic differences (post minus pre) during the heat test minus changes during the thermoneutral test. Genes related to interleukins and cellular stress were significantly down-regulated in participants with a history of EHS compared to their non-EHS counterparts. Suppression of these genes may be associated with susceptibility to exertional heat injury. Prospective research is required to determine whether similar gene expression profiling can be potentially used as blood biomarkers to predict susceptibility to EHS. Highlights: Gene expression profiling may assist in predicting heat tolerance. Genes for immune/inflammatory and stress responses were suppressed in EHS subjects. Future research should examine genetic markers to risk-stratify for EHS.